Pemanfaatan Media Permainan Monopoli dalam Meningkatkan Minat Belajar Siswa pada Materi Keberagaman Indonesia di SDN Pandian 1 - Adelia Carera; Agus Wahdian; Yeni Puji Astuti (Mataram University, 2026)
This study is motivated by the issue of low learning interest among third-grade students at SDN Pandian 1 in understanding the diversity of Indonesia, which is largely caused by conventional lecturing methods that lead to passive learning and boredom. This research aims to describe and analyze in depth the implementation of Indonesian diversity monopoly game media in enhancing students' learning interest. A qualitative descriptive method with a case study design was employed, involving 23 third-grade students at SDN Pandian 1 Sumenep. Data were collected through participatory observation during learning activities, semi-structured interviews with the classroom teacher and student representatives, and documentation. The collected data were analyzed through qualitative processing, descriptive analysis, and conclusion drawing. The findings demonstrate that utilizing modified monopoly game media contextually integrated with Indonesian cultural topics significantly increases students' learning interest. This improvement is evidenced by the fulfillment of four key indicators of learning interest: expressions of enjoyment during learning, strong attraction toward visual media and game cards, sustained concentration, and active participation in group interactions. The incorporation of game elements—such as challenge cards, image guessing, and opportunity cards—not only simplifies complex theoretical concepts but also fosters character traits such as honesty, courage, and teamwork among students. Consequently, the modified monopoly game media proves to be an effective and interactive alternative for elementary school teachers to create a dynamic learning environment and elevate students' interest in cultural diversity topics.